A novel microbial - Bioelectrochemical sensor for the detection of n-cyclohexyl-2-pyrrolidone in wastewater. (10th September 2019) - Kannan, Palanisamy; Jogdeo, Prasanna; Mohidin, Abeed Fatima; Yung, Pui Yi; Santoro, Carlo; Seviour, Thomas; Hinks, Jamie; Lauro, Federico M.; Marsili, Enrico
Abstract: We report the detection of volatile organic compound 1-cyclohexyl-2-pyrrolidone (CHP), in a bioelectrochemical system inoculated with Escherichia coli and supplemented with redox mediator 2-hydroxy-1, 4-naphthoquinone (2-HNQ), using a functionalized carbon nanotube-coated screen-printed electrode (CNT-SPE) modified with –COOH and -NH2 functional groups. Addition of CHP decreased current output of the bioelectrochemical system, thus enabling rapid detection of CHP concentration. Under optimal conditions, the H2 N-CNT-SPE was the best performing and a limit of detection (LOD) of 0.4 mg L −1 was achieved. The proposed sensor showed low interference from other inorganic and organic components. These results outline a viable strategy for detecting organic contaminants in environmental monitoring applications. Graphical abstract: We report bioelectrochemical detection of 1-cyclohexyl-2-pyrrolidone (CHP), a volatile organic compound and a common contaminant in industrial wastewater using a carbon nanotubes-coated screen-printed electrode. The proposed sensor measures concentration of CHP through the variation of current output from Escherichia coli cells following exposure to CHP.Image 1 Highlights: A microbial-bioelectrochemical sensor was developed to detect 1-cyclohexyl-2-pyrrolidone (CHP). Under optimal conditions, the limit of detection for CHP was 0.4 mg L −1 . The sensor has low cost, good reproducibility and is suitable for environmental monitoring.